MODEL PENINGKATAN PENDAPATAN NELAYAN MELALUI INDUSTRI PENGOLAHAN ABON IKAN DENGAN SISTEM DINAMIK DI PASIE NAN TIGO - PADANG - Dwi Marsiska Driptufany; Iswandi Umar; Indang Dewata; Fajrin Fajrin; Aprizon Putra; Arman A; Henny Yulius; Mira Hasti Hasmira; Muhammad Hidayat; Ramadani Yusran (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
Caught fish that have been processed into abon fish increase the sale value of fish. Increasing the selling value of fish and developing business opportunities can increase fishermen's household income and become one of the solutions to poverty in coastal regions. This study aims to analyze the factors that influence the production of the catch and income of traditional fishermen's fishing business. This study aims to analyze a dynamic system model of increasing fishermen's income through the abon fish processing industry in Pasie Nan Tigo Village, Koto Tangah Sub-district - Padang City. This study uses a dynamic systems modeling approach in analyzing the added value of abon fish processing. The results showed that in a scenario with a distribution proportion of 70%: 30%, the sales value of products that undergo processing (abon fish) is higher than raw fish sold without undergoing any processing. The ratio of the sales value between processed abon fish to raw fish sold without undergoing any processing is 115:100. This means that the same volume of fish processing (abon fish) has increased the sale value of raw fish by 15%. This sales value ratio will certainly increase fishermen's income.